2008
DOI: 10.2137/1239099041838049
|View full text |Cite
|
Sign up to set email alerts
|

Germination: a means to improve the functionality of oat

Abstract: The biochemical and physiological reactions of germination have long been utilised to produce barley malt for brewing and other purposes. Also some oat malt has been produced as raw-material of ale and stout production. The main goals of malting have been the degradation of grain storage components to soften the kernel structure, synthesis of amylolytic enzymes and production of nutrients for brewing yeast. Also flavour and colour attributes have been important. During the recent years interest has arisen also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 71 publications
(73 reference statements)
2
74
0
4
Order By: Relevance
“…Superheated steam processing of oat is found to be effective in deactivation of peroxidase in oat groats (Head et al 2010). Germination Germination of cereal seed has been used for centuries to soften the kernel structure, improve its nutritional value, reduce antinutritional effects and improve the functionality of oat seed proteins (Kaukovirta-Norja et al 2004). Skoglund et al (2008) reported an increase in avananthramide content of oat during germination.…”
Section: Processing Of Oatsmentioning
confidence: 99%
“…Superheated steam processing of oat is found to be effective in deactivation of peroxidase in oat groats (Head et al 2010). Germination Germination of cereal seed has been used for centuries to soften the kernel structure, improve its nutritional value, reduce antinutritional effects and improve the functionality of oat seed proteins (Kaukovirta-Norja et al 2004). Skoglund et al (2008) reported an increase in avananthramide content of oat during germination.…”
Section: Processing Of Oatsmentioning
confidence: 99%
“…Especially in oats, garmination has been reported to increase the bioavailability of the proteins due to the increase in the free amino acid content (Tian et al 2010). Several studies have shown an increase of approximately 20% in AVA content in oat grains following the germination process (Bryngelsson et al 2002;Kaukovirta-Norja et al 2004;Skoglund et al 2008;Hübner & Arendt 2013). This increase primarily occurred due to the activation of hydroxyanthranilate N-hyroxycinnamoyl transferase Figure 1.…”
Section: Effect Of Germinationmentioning
confidence: 99%
“…Moreover, reports have markedly studied starch and proteins degradation in the cereals endosperm during germination as it is implicated in malting and food industries 55 57 . However, there have been few reports on cereal lipid degradation during germination, and some studies have been concerned with only how oat oil processing can interfere in food industry 58 . Lehtinen et al.…”
Section: Proteinsmentioning
confidence: 99%
“…59 demonstrated that some oat lipid fractions were susceptible to be normally used at high temperature. Also, Kaukovirta-Norja et al 58 noted that oat lipids stability and their prevention of off-flavour formation are effective in oat processing industry due to the fact that oat has a high lipid content and a high native lipolytic activity. Therefore, the oil mobilization in the cereals endosperm has not been well investigated.…”
Section: Proteinsmentioning
confidence: 99%